Instantaneous determination of chemical composition of Festuca sp. and Dactylis sp. at two different cut times using near infrared spectroscopy (NIRS) - Poblaciones M.J.; Rodrigo S.; Simões N.; Tavares de Sousa M.M.; Bagulho A.; Olea L. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Near infrared spectroscopy (NIRS) was explored as a technique to predict crude protein, moisture, acid detergent fibre (ADF), neutral detergent fibre (NDF), acid detergent lignin (ADL) and digestibility. The sample set consisted of 123 samples of Festuca arundinacea Schreb and 111 of Dactylis glomerata L. The samples were measured by reflectance NIR in a 1100-2500 nm range. NIR models were developed based on a partial least square regression (PLSR) using different smoothing treatments like absorbance, first derivate and normalization. Calibration models established by near infrared spectroscopy (NIRS) were found to be suitable for the rapid, accurate and non-destructive quantification of Dactylis glomerata L. and Festuca arundinacea Schreb components. Crude protein, moisture and ADF were predicted with an excellent precision (R>0.90). NDF and digestibility calibrations were good because, in spite of having a good coefficient of determination (R>0.90), the errors in Festuca arundinacea Schreb, are slightly high. ADL had a poor prediction power due to the low coefficient of determination (R<0.75).
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)